MC1R Deficiency Enhances Th1 Response and Impairs Regulatory T Cell Homeostasis In Nephrotoxic Serum Nephritis - Chen, Bohan (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.